Resistência a antimicrobianos e genotipagem de amostras de Escherichia coli isoladas de água para consumo da mesorregião de Belo Horizonte e detecção direta de integrons nas águas - João Fernando Gonçalves Ferreira (2018)
The low microbiological quality of water is associated with a mortality rate of 2,9 million people per year. Among the agents of water-borne diarrheal disease Escherichia coli should be highlighted. The organism presents a heterogeneous drug resistance profile. Thus, aquatic environments may act as a route for dissemination of antimicrobial resistant microorganisms between human populations. This study targeted the genotyping and the investigation of aspects related to antimicrobial drug resistance in E. coli samples obtained from drinking water from the mesoregion of Belo Horizonte and also aimed to search for integrons directly from water sources in the municipality of Ouro Preto. A total of 423 E. 10 coli sisolates were used in this study. Evaluation of the antimicrobial susceptibility profile was performed by disk diffusion method and indicated that 146 samples showed resistance to at least one antimicrobial and 37 showed to be multiresistant. PCR was performed to search for integrons and gene cassettes and isolates presented positive results for the presence of class 1 integrons and clinical class 1 integrons, two of which have associated gene cassettes. Integrons class 2 were not observed. Sequencing of the hypervariable region of the rpoB gene allowed the genotyping of samples and three genetic groups were differentiated. Real-time PCR was employed in order to investigate the occurrence of class 1 integrons in drinking water. Fourteen samples were tested and three presented intI1 quantification results above the minimum detection limit. Thus, it can be concluded that some of these waters used for human consumption are acting in the transmission of different variants of E. coli, as well as in the dissemination of resistance genes and genetic elements associated with the expression of antimicrobial resistance. Consequently people that drink these waters are exposed to the potential risks associated with the consumption of non-potable water.